IPO AS AN EFFECTIVE INSTITUTION AND A PRECONDITION OF CORPORATE RESTRUCTURING FOR AGRICULTURAL COMPANIES - D. Baiura; D. Sytenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The key factors of investment attractiveness of the agricultural sector of Ukraine and the need to finance its development through the use of the IPO are analyzed. The main advantages and disadvantages received by any company after passing the IPO are demonstrated. The analysis of the results of the IPO of agricultural enterprises of Ukraine is conducted. Such areas of corporate restructuring as organization of a new corporate structure, bringing system of a corporate governance to the principles of OECD, increased transparency of financial – economic and not financial reporting, optimization of financial management and business process, and also appropriate measures for each of these areas in order to ensure an effectiveness of the IPO are proposed.